A Study on Interpersonal Relationship Between Leaders and Employees with Reference to Commitment Towards Kedah State Development Corporation, Malaysia - Hanif, Hassan (2012)
Employee commitment has emerged as one of the most important topics in the sphere of human resource management. It stands for the extent to which the employees are fully involved in his/her work and will act in a way that furthers their organization interests. The main objective of this study is to identify the interpersonal relationship between leadership style, of leadership personality and leaders’ attitude with employees’ commitment. A total of 120 questionnaires were distributed to the respondents in Kedah State Development Corporation (KSDC) and 101 of them were returned for analysis. Data were collected and analyzed using the Statistic Package for Social Science (SPSS) version 16.0. The study indicates that there is a significant relationship between leaders’ attitude and leadership personality. However, leadership style does not have a significant influence to organization commitment.